Internalized stigma and its correlates in families of persons with mental illness in Qatar: a cross-sectional study - Vahe Kehyayan (21241649) (2024)
Persons with mental illness (PWMI) experience rejection, isolation, and discrimination in employment, education, and housing due to the prejudice associated with the illness. Families affiliated with PWMI often internalize the public’s prejudice towards mental illness. Such internalized stigma can further impact the health and quality of life of both PWMI and their families. This study aimed to examine the level and correlates of internalized stigma in family members of PWMI in Qatar. A cross-sectional study of 106 family members was conducted using the Family Internalized Stigma Mental Illness Scale. The mean stigma score was 2.04 suggesting a mild level of stigma overall. Being married was found to be a predictor of higher levels of internalized stigma, while having college education or higher predicted lower levels of stigma. The overall stigma scores among family members were not high, which may reflect the protective stance families take towards about their relatives with mental illness. Some sociodemographic attributes predicted trends in internalized stigma among our surveyed sample. Future research efforts in this area may help increase understanding of internalized stigma in this population to inform stigma reduction efforts. Other Information Published in: Current Psychology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12144-024-06686-y